Usia Menopaouse pada Wanita di Wilayah Kerja Puskesmas Rambah Kabupaten Rokan Hulu - Sepduwiana, Heny (Jurnal Martenity and Neonatal, 2016)
Menopause is the phase changing of a woman from productive to non-productive phase. This happens at the end of the last menstrual cycle when a woman has not got menstrual cycles for at least 12 months. Womenat the age of menopause will get more health risks due to reduce of estrogen hormone. Currently, the age of menopause is accelerating, while the woman's life expectancy is getting longer. This research was to determine the average age of menopause and the factors related to the occurrenceof menopause in women at 45 to 55 years old. This research was conducted in working area of Rambah Public Health Centre, Rokan Hulu regency in July 2015. The type of the research was an analytic qualitative method and cross sectional design.The population was 326 people with a sample of 120 people were taken by systematic random sampling technique. To analyze the data, researcher used ANOVA test, T test, test product moment correlation and multiple linear regressions. This research showed that the average age of menopause phase was 47,6 ± 2,8 year; the results of multivariate analysis showed the menopause age = 39 + 3.1 birth controll usage + 0,2 age of the last birth + 0,1 consume of nuts, - 0,3 menarche.The conclusion of this study are the variables that most influence on the age of menopause is the use of contraception, the consumption of nuts, nutrition status, past child-bearing age and menarche with R² known 0,6. Strategies to slow the menopause in womenare by setting the birth spacing by using hormonal contraception, maintaining nutrition status, in creasing of consumption of foods containing phytoestrogens since childhood.